‘Temporary non-appearance of memory’ among the interviewees: Methodology enhancement in qualitative research for achieving high quality data - Kumar, Pranav; Mohd Mokhtar, Sany Sanuri (2013)
With mounting popularity of qualitative research worldwide, interviews have emerged as one of the foremost and widely used techniques for data collection.However, there has been little research which examines the appropriate timings for conducting an interview which results in attainment of a high quality data.To shed light on ‘when to conduct an interview for highest data quality’ was the purpose of this research.Using a grounded theory approach, this study conducted interviews with selected participants who pondered differently at different times of a day and exhibited considerable variations in their answers’ quality and extent of comprehensiveness.It finally led to development of a theory based on the findings of our research which discovered that at times, there exists ‘Temporary Non-appearance of Memory’ among the interviewees which adversely affects the quality of their responses thus affecting the final outcomes of qualitative research.